The Impact of Innovation and Digitalisation on the Internationalisation Readiness of SMEs in Indonesia: A Resource-Based View Approach - Ivan Widjaja; Sudarmiatin Sudarmiatin; Heri Pratikto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
MSMEs play a dominant role in the Indonesian economy, but their contribution to the international market remains relatively limited. This situation indicates that the readiness for internationalisation of MSMEs remains a significant issue, particularly in relation to innovation and digitalisation capabilities as strategic resources. This study aims to analyse the influence of innovation and digitalisation on the readiness for internationalisation of MSMEs in Indonesia using the Resource-Based View approach. The study employs an explanatory quantitative design with a survey approach involving 200 owners or primary managers of SMEs in East Java, selected via purposive sampling. Data were analysed using SEM-PLS. The results indicate that innovation and digitalisation have a positive and significant influence on the internationalisation readiness of SMEs. Digitalisation demonstrates a stronger influence than innovation. The structural model also exhibits adequate explanatory and predictive power. These findings confirm that internationalisation readiness is determined not only by market opportunities but also by the ability of SMEs to strategically manage innovation and digital technology. The implications of this study emphasise the importance of strengthening innovation and digitalisation capabilities as the foundation for formulating SME development strategies that are better prepared to enter international markets.